Defining Polio: Closing the Gap in Global Surveillance - Bachir Tajaldin (Ubiquity Press, 2015)
Background: By late 2012 the Global Polio Eradication Initiative (GPEI) had nearly eradicated this ancient infectious disease. Successful surveillance programs for acute flaccid paralysis however rely on broad governmental support for implementation. With the onset of conflict, public health breakdown has contributed to the resurgence of polio in a number of regions. The current laboratory based case definition may be a contributory factor in these regions. Objective: We sought to compare case definition rates using strict laboratory based criteria to rates obtained using the clinical criteria in modern day Syria. We also sought to examine this distribution of cases by sub-region. Methods: We examined the World Health Organization (WHO) reported figures for Syria from 2013–2014 using laboratory based criteria. We compared these with cases obtained when clinical criteria were applied. In addition we sought data from the opposition controlled Assistance Coordination Unit which operates in non-Government controlled areas where WHO data maybe incomplete. Cases were carefully examined for potential overlap to avoid double reporting. Findings: Whilst the WHO data clearly confirmed the polio outbreak in Syria, it did so with considerable delay and with under reporting of cases, particularly from non-government controlled areas. In addition, laboratory based case definition led to a substantial underestimate of polio (36 cases) compared with those found with the clinically compatible definition (an additional 46 cases). Rates of adequate diagnostic specimens from suspected cases are well below target, no doubt reflecting the effect of conflict in these areas. Conclusions: We have identified a gap in the surveillance of polio, a global threat. The current laboratory based definition, in the setting of conflict and insecurity, leads to under diagnosis of polio with potential delays and inadequacies in coordinating effective responses to contain outbreaks and eradicate polio. Breakdown in public health measures as a contributing factor is likely to result in a resurgence of previously controlled infectious diseases. The clinical definition should be reinstituted to supplement the lab-based definition.